Pancreatic fistula after a pancreaticoduodenectomy for ductal adenocarcinoma and its association with morbidity: a multicentre study of the French Surgical Association. Issue 1 (6th March 2013) - Addeo, Pietro; Delpero, Jean Robert; Paye, Francois; Oussoultzoglou, Elie; Fuchshuber, Pascal R; Sauvanet, Alain; Sa Cunha, Antonio; Le Treut, Yves Patrice; Adham, Mustapha; Mabrut, Jean‐Yves; Chiche, Laurence; Bachellier, Philippe; et al.
Abstract Backgrounds A pancreatic fistula (PF) is the most relevant complication after a pancreaticoduodenectomy (PD). This retrospective multicentric study attempts to elucidate the risk factors and complications of a PF in a large cohort of patients undergoing a PD for ductal adenocarcinoma. Methods Using a survey tool, clinical data of 1325 patients undergoing a PD for ductal adenocarcinoma at 37 institutions, between January 2004 and December 2009, were collected. Peri‐operative risk factors associated with PF and its association with morbidity and mortality were assessed. Morbidity and PF were graded according to the ISGPF (International Study group for pancreatic fistula) definition and the Dindo–Clavien classification. Results Overall PF, mortality, morbidity and relaparotomy rates were 14.3%, 3.8%, 54.4% and 11.7%, respectively. PF occurred more frequently after a pancreaticojejunostomy (PJ) compared with a pancreaticogastrostomy (PG) (16.8% vs. 10.4%; P = 0.0012). Independent risk factors for PF by multivariate analysis were absence of pre‐operative diabetes (P = 0.0014), PJ reconstruction (P = 0.0035), soft pancreatic parenchyma (P < 0.0001) and low‐volume centre (P = 0.0286). Clinically relevant PF (grade B and C) and severe complications (Dindo–Clavien grade IIIB, IV, V) were significantly more frequent after PJ than PG (71.6% vs. 28.3%; P = 0.030 and 24.8% vs. 19.1%; P = 0.015, respectively). Overall mortality and relaparotomy rates were similar after PG and PJ. Conclusions A soft pancreatic parenchyma, the absence of pre‐operative diabetes, PJ and low‐volume centre are independent risk factors for PF after PD for ductal adenocarcinoma. A significantly higher incidence and clinical severity of PF are associated with PJ.